Effect of NiO and MoO3 addition on the crystallinity and mechanical properties of α-cordierite and β-cordierite in the MgO-Al2O3-SiO2 system - Zalapa Garibay, Manuela Alejandra (2019)
The cordierite is one of the most important phases within the MgO-Al2O3-SiO2 (MAS) system. In this study, the crystallization and microstructure of cordierite was analyzed. Four samples were prepared, which were subjected to a thermal treatment at a temperature of 1200 °C with a permanence time of 2 h. The temperature of the thermal treatment was selected depending on the critical working temperature, specific applications such as coatings of glass ceramic materials, according to the literature review. Characterization was performed by thermal analysis, X-ray diffraction, scanning electron microscopy, microhardness tests and nano-indentation to observe the effect of NiO (0–3 %wt) addition, on the formation and crystallization of α and β cordierite phases. The X-ray diffraction results showed that the formation of α-cordierite was promoted by crystallization of several metastable phases with the addition of NiO. Meanwhile a decrease of the β-cordierite phase was observed, to give rise to formation of α-cordierite as %wt. NiO increases. The average crystal size of the crystalline phases was larger in the sample without NiO addition, and the sizes of the crystals, especially α-cordierite decrease with higher concentrations of NiO, and the crystals within the domains become smaller, which results in a microstructure and better mechanical properties (hardness = 8–11 GPa and Effective elastic modulus = 11–14 GPa), than those reported in the lit erature (hardness = 7–8 GPa and Effective elastic modulus = 10–13 GPa).